Some things are not forgotten : a Pawnee family remembers - Blaine, Martha Royce, 1923- (University of Nebraska Press, 1997)
The Blaine family were among the Pawnees forcibly removed to Indian Territory in 1874-75. By the early twentieth century, disease and starvation had wiped out nearly three-quarters of the reservation's population. Government boarding schools refused to teach Pawnee customs and language, and many Pawnees found themselves without a community when their promised land was allotted to individuals and the rest sold as "surplus" to white settlers. Where did the Blaine family find the resilience to cope with the continual assault on their dignity and way of life? In Some Things Are Not Forgotten, Martha Royce Blaine reveals the strengths of character and culture that enabled them to persevere during the reservation years.